2017
DOI: 10.4168/aair.2017.9.5.410
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Immediate-Type Food Allergy in Korean Schoolchildren in 2015: A Nationwide, Population-based Study

Abstract: PurposeThis study aimed to determine the prevalence of immediate-type food allergy (FA) among schoolchildren in Korea.MethodsA nationwide, cross-sectional study was performed in September 2015. A stratified random sample of 50,000 participants was selected from children and adolescents aged 6-7 years (n=17,500), 9-10 years (n=17,500), 12-13 years (n=7,500), and 15-16 years (n=7,500). Parents were asked to complete a questionnaire on the detailed history of immediate-type FA.ResultsA total of 32,001 (64.0%) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 40 publications
1
55
0
2
Order By: Relevance
“…The overall incidence of anaphylaxis in representative Asian centers ranged between 2.5 and 38 per 100 000 person‐years . Other studies reported an anaphylaxis prevalence of 0.003% from large hospital or insurance‐based databases to 1% in a study based on self‐reported anaphylaxis symptoms . The reported incidence of anaphylaxis differed considerably between countries.…”
Section: Global Anaphylaxis Reporting and Incidencementioning
confidence: 98%
See 3 more Smart Citations
“…The overall incidence of anaphylaxis in representative Asian centers ranged between 2.5 and 38 per 100 000 person‐years . Other studies reported an anaphylaxis prevalence of 0.003% from large hospital or insurance‐based databases to 1% in a study based on self‐reported anaphylaxis symptoms . The reported incidence of anaphylaxis differed considerably between countries.…”
Section: Global Anaphylaxis Reporting and Incidencementioning
confidence: 98%
“…Likewise, the median age of onset of wheat allergy in Thai children was 6 months of age and 55.3% presented with anaphylaxis upon first exposure . Wheat and buckwheat were also major allergens in Japanese and Korean children (after egg and milk) and adults . In northern China, cereals and wheat were the top food allergens implicated in anaphylaxis, especially in adolescents and adults .…”
Section: Anaphylaxis Triggers—east Vs Westmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Hasta 2 % de los adultos en Estados Unidos padece APLV 8 y 1 % en Europa, 9 pero en países como Corea no supera 0.3 %. 10 La prevalencia de APLV en adultos es más baja porque la alergia en los infantes se resuelve con el transcurso de los años. 11 En un estudio de cohorte en Europa se encontró una incidencia de 0.74 % de APLV durante los…”
Section: Antecedentesunclassified